Application of reactive transport modeling to growth and transport of microorganisms in the capillary fringe - Hron, Pavel; Bastian, Peter; Ippisch, Olaf (Vadose zone journal, 2015)
We use reactive transport modeling to facilitate the description of a large variety of complicated phenomena in porous media including transport, diffusion, microbiological growth, adhesion, and phase exchange. The model results are compared with the flow-through laboratory experiments with microorganisms in saturated and unsaturated porous media.